Two Indonesian Children Acquire Bahasa Indonesiain Different Ways: Reconsidering Theories - Himpun Panggabean (International Journal of Educational Research & Social Sciences, 2021)
In this research, two participants, my children Ceria Panggabean (CP) and her younger brother Patuan Noel Panggabean (PNP) acquire their first language Bahasa Indonesia in different ways. CP acquires the language in normal stages of language acquisition that matches the theory of Universal Grammar (UG) endorsed by Behaviorism and Social Interactionism but PNP acquires it beyond critical period. CP grows normal physically but PNP cannot stand and walk but crawls. When his physical impairment is overcome, especially when he is able to run, he acquires the language so fast that when he is over 3,5 years, his language proficiency is in the same level as PNP’s. Based on this, at least as hypothesis, abnormal language acquisition or Specific Language Impairment (SLI) may be due to not only brain and organs of speech impairments but also abnormal physical growth that might affect brain. It is also revealed that UG called Nativism is endorsed by empirical phenomenon called Behaviorism and social interaction called Social Interactionism. Besides, criticisms on certain concepts of linguists and recommendations are noted. The data are gathered using methods of Parents’ Diary and Observational Studies via audiotape, to study how each of them goes through acquisition stages, and Experimental Studies with Nipple Sucking Rate test in cooing or prelinguistic stage to find out whether or not they are hearing or deaf. The research covers the acquisition of phonology, morphology, syntax, and semantics as well as their developments.